Kult svatých a dynastická propaganda na dvoře Báthoryů v 16. století - Tomáš Kruppa (Theatrum Historiae)
The Báthory family, as a newly established dynasty, placed sacred cult and the founding legend at the center of its legitimacy. It was connected to our first holy kings in the Árpád dynasty (St. Stephen, St. Ladislaus) and to St. Sigismund, who was considered a Hungarian saint, who was also a common Central European saint. The other source of legitimacy was linked to the legendary dragon-killing founder of the genus, behind which the cult of St. George emerged, which, together with the cult of King St. Ladislaus, was very popular among Hungarians fighting with the Turks. With the outbreak of the Fifteen Years' War, both means of legitimacy received great emphasis in Zsigmond Báthory's war propaganda targeting Hungary and abroad. This culminated in the 1535 campaign in the Highlands; the prophecies and prophecies of the fall of the Turkish Empire, which would proliferate at the end of the century, and which would be brought to an end by a valiant ruler appearing in the east, were already present in the royal propaganda.